CONCRETE FOR ANTARCTICS - AGGREGATE AND MIX DESIGN FOR McMURDO AREA. - Keeton,John R.; Stehle,Nancy S. (1968)
The ability to mix, cast and properly cure concrete for use in construction of land-based polar facilities would provide permanency to installations as well as reduce the quantity of imported construction materials. To determine the feasibility of using Portland cement concrete at McMurdo Station, Antarctica, investigations were made of local aggregate materials and of suitable concrete mixes. (Author)